A Study of the Structure, Properties, and Sorption Activity of Oil Sorbents Based on the Secondary Cellulose-Containing Raw Materials of Buckwheat Cereal Production - Anton Mostovoy; Natalia Eremeeva; Andrey Shcherbakov; Marina Lopukhova; Sholpan Ussenkulova; Elvira Zhunussova; Amirbek Bekeshev (Molecules)
The possibility of using the secondary cellulose-containing raw material resource of the cereal production of buckwheat, namely, its husk, as sorbents for the collection of oil and oil products is shown. In order to increase the yield of the finished product, develop porosity, and improve the sorption characteristics of the buckwheat husk, methods for its physical and chemical modification are proposed. The effect of the modification modes on the parameters of the porous structure, as well as the sorption capacity of the developed materials for various types of oil products, was studied. The selection of the optimal parameters of the buckwheat husk modification was carried out, ensuring the production of effective unsinkable sorbents based on the buckwheat husk with a reserve buoyancy of more than 20 days and a high sorption capacity of sorbents for oil of up to 6.1 g/g and waste motor oil of up to 4.9 g/g. The use of the buckwheat husk as a sorbent allows not only the elimination of oil pollution on both water and surfaces but also solving the problem of the disposal of agricultural waste.